(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article presents a line of object poetics that articulates animation theater, dance and technologies. Some exposed aspects are simultaneously technical, aesthetic and political, forming an impro-compositional zone understood as a horizontal material system in which the acting body is also understood as matter. This environment has been called the Machinic Zone and the sharing of some of its aspects aims to expand the possibility of collaborating with tools in the teaching and artistic field, strengthening the plurality of Animation Theater.